2021
DOI: 10.1159/000517493
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First Wave COVID-19 Crisis on Dialysis Parameters of COVID-Free Hemodialysis Patients: A NephoCare France Longitudinal Retrospective Cohort Study

Abstract: <b><i>Background:</i></b> Chronic hemodialysis (HD) patients are at high risk of severe COVID-19 with a high risk of death. The organization of dialysis units to treat chronic HD patients with COVID-19 is demanding to prevent virus transmission both in COVID-free patients and the staff. These constraints may have an impact on the dialysis delivery to COVID-free HD patients. We report our experience in French NephroCare (NC) centers. <b><i>Methods:</i></b> We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The rate of hospitalization unrelated to COVID-19 also declined significantly 25 , suggesting difficulties in accessing care. In addition, logistical constraints during the first wave resulted in decreased weekly dialysis time in non-infected patients 30 . Furthermore, a sharp reduction in kidney transplantation occurred during the first wave in 22 countries worldwide 31 .…”
Section: Disease Coursementioning
confidence: 99%
“…The rate of hospitalization unrelated to COVID-19 also declined significantly 25 , suggesting difficulties in accessing care. In addition, logistical constraints during the first wave resulted in decreased weekly dialysis time in non-infected patients 30 . Furthermore, a sharp reduction in kidney transplantation occurred during the first wave in 22 countries worldwide 31 .…”
Section: Disease Coursementioning
confidence: 99%
“…Therefore, it is conceivable that the modifications of the usual medical care also had an influence on the clinical management and outcomes of diseases not directly related to COVID-19. In this regard, a recent large retrospective study on a French cohort of hemodialysis patients (HD) showed that the quality of HD delivered to COVID-19-free HD patients was negatively impacted because of the strong constraints on Nephrology units’ organization related to the pandemic [ 8 ]. Consistently, in this study, we investigated whether the COVID-19 pandemic could have had an impact on intrahospital AKI incidence and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has greatly affected the patient population with end-stage kidney disease (ESKD). Patients on hemodialysis (HD) are more vulnerable to infection due to treatment with other patients in a confined space and shared transportation ( 1 ) and also at higher risk for adverse outcomes ( 2 ). Identifying patients at risk for adverse outcomes might aid individualized treatment decisions such as the need for hospitalization and more intensive monitoring.…”
Section: Introductionmentioning
confidence: 99%